Pengaruh Green Marketing dan Citra Merek terhadap Pembelian Ulang melalui Kepuasan Konsumen sebagai Variabel Intervening pada Produk Torufarm Palu - Nuraini, Intan; Muzakir, Muzakir; Ponirin, Ponirin; Buntuang , Pricylia Chintya Dewi (Studi Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: The purpose of this research is to analyze the effect of green marketing and brand image on repurchases through customer satisfaction as an intervening variable in Torufarm Palu products. Methodology: This research methodology is quantitative and was used to examine consumer purchases at Torufarm Palu. The sampling technique used in this study was nonprobability sampling by using purposive sampling. A sample of 120 respondents was selected based on Sugiono's statement. The analysis method used was SEM-PLS. Results: The results showed that green marketing and brand image have a positive effect on customer satisfaction, green marketing has a positive effect on repeat purchases, brand image has a negative effect on purchases, and customer satisfaction has a positive effect on purchases. In addition, there is an indirect relationship between green marketing and brand image to repurchase through customer satisfaction. Conclusions: Torufarm Palu can improve customer satisfaction through its green marketing and brand image. The green marketing, demonstrated by the sale of fresh fruits and vegetables, has proven effective in influencing consumers to repurchase Torufarm Palu's products. However, the brand image does not significantly influence repeat purchases, as visitors tend to overlook the company's brand image due to the large number of competitors. Limitations: The research variables are limited to aspects that can increase consumer satisfaction and encourage companies to improve their services to maintain the company's brand image. This research is limited to aspects of green marketing and specifically focuses on repeat purchases through customer satisfaction. Contribution: This study contributes to the literature on green marketing and brand image by providing a detailed analysis of the factors that can influence repeat purchases through customer satisfaction with torufarm products.